1972
DOI: 10.1085/jgp.59.5.519
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Vasopressin Action on the Toad Bladder

Abstract: Toad bladders were challenged with vasopressin at one temperature, fixed on the mucosa with 1% glutaraldehyde, and then subjected to an osmotic gradient at another temperature. Thus, the temperature dependence of vasopressin action on membrane permeability was distinguished from the temperature dependence of osmotic water flux. As the temperature was raised from 200 to 38 0 C, there was a substantial increase in the velocity of vasopressin action, but osmotic flux was hardly affected. In this range of temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1973
1973
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…Thus, there is strong evidence to support the inference that cold temperature decreases the fluidity of the toad bladder. Despite this inference and despite the fact that lowering the temperature decreases the rate of osmotic flow of water in toad bladders with "fixed" water permeability (Eggena, 1972), in our studies the flow of water decreased more slowly at 2~ than at room temperature (Table 1, expt. A).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Thus, there is strong evidence to support the inference that cold temperature decreases the fluidity of the toad bladder. Despite this inference and despite the fact that lowering the temperature decreases the rate of osmotic flow of water in toad bladders with "fixed" water permeability (Eggena, 1972), in our studies the flow of water decreased more slowly at 2~ than at room temperature (Table 1, expt. A).…”
Section: Discussioncontrasting
confidence: 74%
“…Earlier studies with inhibitors of energy production had also suggested that metabolic energy was necessary for the onset of action of ADH on water flow (Handler, Petersen & Orloff, 1966). In addition, the direct relationship between temperature and water flow has been studied in tissues where water permeability was "fixed" with glutaraldehyde (Eggena, 1972). In contrast, events involved in the offset of action of ADH have not been evaluated.…”
mentioning
confidence: 99%
“…Toads were doubly pithed and their urinary bladders were then resected and tied to the ends of glass cannulas with the mucosa on the inside and the serosa on the outside of the bladder sac (8,9 To measure the net mucosal-to-serosal movement of urea across the bladder wall (Tables I-V), bladders were filled with 7-ml urea solutions and suspended each into separate 10-ml serosal fluid baths that were changed at 15- Glutaraldehyde has been used previously to lock the water permeability barrier of the toad bladder in various stages of response to hormone (10)(11)(12). The same procedure was used here to preserve the effect of vasopressin on the permeability of the bladder to urea.…”
Section: Methodsmentioning
confidence: 99%
“…We had observed previously (10)(11)(12) that the water permeability barrier of the toad bladder could be virtually "locked" in various stages of response to vasopressin by exposing the mucosal surface of the bladder wall for 5 min to a 1 % solution of glutaraldehyde. These fixed bladders were found to retain about 78% of their prefixation permeability to water when removed to hormone-free solutions.…”
Section: Re Sultsmentioning
confidence: 99%
“…The mild glutaraldehyde (E. Merck, Darmstadt) fixation [12][13][14] of the apical membrane structures was performed with 2% glutaraldehyde in water or KC1 solution without buffer, according to the experimental protocol, for a period of 2 rain followed by thoroughly rinsing the outer membrane surface with distilled H20 or KC1 solution to remove the fixative.…”
Section: Methodsmentioning
confidence: 99%